The Influence of Murabahah, Musyarakah, Mudharabah and Qardh on the Profitability of Islamic Commercial Banks - Nurjanah, Feby; Budiantoro, Harry; Gunawan, Andri; Zhafiraah, Nazma Riska; Ningsih, Hestin Agus Tantri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
This research aims to determine how the effect of Murabahah, Musyarakah, Mudharabah and Qardh financing on profitability at Islamic Commercial Banks for the period 2017-2021. The research method used in this research is quantitative research method. The data collection method was carried out through documentation using secondary data taken from the financial statements of each Islamic commercial bank in 2017-2021. The sampling method used purposive sampling technique with the analysis technique used was multiple linear regression using the SPSS version 26 application. The results showed that none of the Murabahah variables had an effect on profitability. Musyarakah variable has a negative and significant effect on profitability. Meanwhile, Mudharabah and Qardh variables have a positive and significant effect on profitability. The managerial implication is that Murabahah as the type of financing most often used by Islamic banks provides a relatively stable fixed income because it uses the principle of a fixed margin agreed upon in advance. Musharakah involves joint capital participation between the bank and the customer, where the bank gets a share of the profits or bears the losses according to the agreement. The bank acts as the capital owner (shahibul maal) who hands over funds to the business manager (mudharib) and gets a share of the profits.